2011
DOI: 10.1536/ihj.52.23
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Menstrual Cycle on P Wave Dispersion

Abstract: SummaryFemale gender is an independent risk factor for some types of arrhythmias. We sought to determine whether the menstrual cycle affects P wave dispersion, which is a predictor of atrial fibrillation. The study population consisted of 59 women in follicular phase (mean age, 29.3 ± 7.7 years) (group F) and 53 women in luteal phase (mean age, 28.1 ± 6.8 years) (group L). The ECGs of 35 patients (mean age, 26.4 ± 4.5) were obtained in both follicular and luteal phase. Both groups underwent a standard 12-lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Indeed, prior studies have assessed P-wave parameters throughout the menstrual cycle and noted that P-wave duration is substantially increased in the luteal phase. 24 Among women who did report taking prior hormone therapy, we observed a very modest but significant increase in midlife PR interval and in P-wave duration. Exogenous hormone therapy use may obscure the relationship between endogenous hormone exposure from a longer reproductive period duration and P-wave parameters, which would explain our findings of effect modification by hormone therapy use.…”
Section: Discussionmentioning
confidence: 70%
“…Indeed, prior studies have assessed P-wave parameters throughout the menstrual cycle and noted that P-wave duration is substantially increased in the luteal phase. 24 Among women who did report taking prior hormone therapy, we observed a very modest but significant increase in midlife PR interval and in P-wave duration. Exogenous hormone therapy use may obscure the relationship between endogenous hormone exposure from a longer reproductive period duration and P-wave parameters, which would explain our findings of effect modification by hormone therapy use.…”
Section: Discussionmentioning
confidence: 70%
“…Various studies have shown that due to hormonal fluctuations in the organism during menstrual cycle, there may occur changes in aerobic, anaerobic and muscle strength. In addition, various authors have researched and are still continuing to research whether different phases of menstrual cycle have an influence on risk of injury (Beynonn et al, 2006), anaerobic power (Tsampoukos et al, 2010), sport performance (Oosthuyse et al, 2010), muscle strength (Loureiro et al, 2011), flexibility (Bell et al, 2009) and cardiovascular mechanisms (Bai et al, 2009;Fu et al, 2010;Karabag et al, 2011). Indeed, while some studies have shown that menstrual cycle phases influence sportive performance (Jaffre et al, 2006;Gordon et al, 2013), other studies show that these phases do not have an influence on performance (Giacomoni et al, 2000;Smekal et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There was a significant correlation between the day of menstrual cycle and P d . But no correlation existed between age, estrogen, progesterone levels, and P d measurements [42]. In an experimental study, 17beta-estradiol was administered to dogs and atrial pacing of 800 min −1 was performed and effective refractory periods (ERP) were evaluated.…”
Section: Discussionmentioning
confidence: 99%